Reconstruction of annual money supply over the long run: The case of England, 1279-1870 - Nuno Palma (European Historical Economics Society (EHES), 2016)
I provide the first annual time series of coin and money supply estimates for about six hundred years of English history. I propose two main estimation methods. The first, which I call the 'direct method', is used to measure the value of government-provided, legal-tender coin supply only. Additionally, I propose an 'indirect method' which relies on a combination of information about nominal GDP with the value of coin supply or M2 known at certain benchmark periods. The latter permits estimating the growth of financial intermediation over time. The new methodologies which I set out here may serve as a blueprint for a similar reconstruction of coin and money supply series for other economies for which analogous data is available.
Keywords: E10; E40; E51; N13; 330; historical money supply; financial intermediation